KEWAJIBAN PENGGUNAAN BAHASA INDONESIA DALAM AKTA NOTARIS BERDASARKAN STUDI KASUS AMAR PUTUSAN PENGADILAN NEGERI JAKARTA BARAT NOMOR 451/PDT.G/2013/PN/JKT.BRT - Aprianti Rita Wulandari (JURNAL ILMIAH NUSANTARA, 2024)
Based on Article 43, Paragraph (1) of the Notary Law (UUJN-P), notarial deeds must be drafted solely in Indonesian and not in any other language due to the use of the term "mandatory" in this provision. The core issue arises because Paragraph (3) allows for deeds to be drafted in a foreign language if the parties involved desire it. This creates a question about the consistency of the mandatory use of Indonesian for notarial deeds while also permitting the use of foreign languages. The aim of this research is to examine and analyze the legal certainty regarding the obligation to use Indonesian in the creation of notarial deeds according to the Notary Law, as well as the legal consequences of this obligation. This study employs normative legal research with a legislative and conceptual approach, utilizing qualitative analysis. Ensuring legal certainty in the obligation to use Indonesian for notarial deeds, as stipulated by Law Number 2 of 2014 on the Notary Office (UUJN), is crucial for maintaining consistent legal standards. UUJN mandates that all notarial deeds must be in Indonesian so that documents can be uniformly understood by all parties and legal institutions in Indonesia. Inconsistencies in enforcing this obligation can render deeds legally invalid and cause legal and administrative harm to the parties involved, as well as difficulties in enforcing agreements or transactions.